Aspects of the tourism market development in the Dobrudgean rural area - Elena Sima (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
The rural area from Dobrudgea has an extensive and highly diversified tourism potential. The main tourist attractions are represented by: natural resources - such as spas and balneo-climateric resorts; religious heritage; cultural and historical heritage; ethnographic and gastronomy elements. The tourism infrastructure in these rural areas is well represented by a good rage of accommodation structures such as small budget hotels or B&Bs. However, by comparison, there are very few leisure and service supply structures such as entertainment facilities, bars, restaurants, theatres, cinemas or shopping facilities. In this context, the objective of this paper is to highlight some of the main characteristics or aspects that characterise the rural tourism market development in the Dobrudgean rural area. The methodology used is based on secondary data analyses under the form of a synthesis of information from articles and studies published in specialty journals, in Government documents as well as in other development strategies dedicated to tourism and the rural space. The findings of this scientific research study argues that the successful rural tourism promotion and development very much depends on an efficient and sustainable exploitation of the existing tourism potential, on the development of a viable network of private small and medium-sized enterprises in the tourism sector and also on the involvement of governmental and non-governmental institutions.
Keywords: R20; L83; 330; rural space; rural tourism market; tourism activities; Dobrudgea